Implementasi Metode Diskusi Untuk Meningkatkan Keaktifan Belajar Dan Hasil Belajar Siswa Kelas XI MPLB Pada Mata Pelajaran OTHK Di SMKN 1 Karanganyar - Brilliant Amira Kusumawati; Hery Sawiji; Winarno Winarno (Politeknik Kampar, 2023)
This study aims to determine the effect of implementing the discussion method on students' learning outcomes and activeness in the OTHK subject in class XI MPLB at SMKN 1 Karanganyar. This research is a classroom action research with 36 students as the recipients of the intervention, while the participants of the action are the OTHK teachers of class XI MPLB, and the researcher as the subject who observes the learning process. Data collection techniques used in this study include tests, observations, and interviews. The results of the study indicate that: (1) the implementation of the discussion method can improve the learning activeness of class XI MPLB students at SMKN 1 Karanganyar, where the activeness score shows an average percentage increase from 50.31% in cycle I to 79.23% in cycle II.; (2) the implementation of the discussion method can improve the academic achievement of class XI MPLB students at SMKN 1 Karanganyar, as evidenced by the comparison of the learning outcomes in cycle I and II, which showed an increase from 82.29 to 93.43. This is due to the improvement in students' understanding of the subject matter, supported by their increased activeness as a form of improving learning quality. Thus, the overall findings of this analysis support the proposed hypotheses.